The influence of offside rule and pitch sizes on the youth soccer players` small-sided games external loads - Vázquez-Guerrero, J.; Casals, M.; Corral-López, J.; Sampaio, J. (Research in Sports Medicine, 2020)
The aim of this study was to identify the correspondence between the workload demands in training sessions and the game performance from elite basketball players, according to their specific positions. Data were collected from a professional men`s basketball team competing in the Spanish Professional League and Euroleague. Players` activity during the training sessions was measured using WIMU PRO® and the game statistics were used as a measure of game performance. Cluster analysis allowed to classify the training workload and the game performance, whereas correspondence analysis allowed to explore their relationship. In essence, there was no correspondence from the higher workloads with the best performances, on the contrary, the small forwards` best performances corresponded to lower training workouts. Despite their importance, the external measures of load need to be complemented with additional (and valid) measures that can be translated to game performance.